Protective Effects of Bronchopulmonary Sequestration (BPS) on the Prognosis of Neonates with Congenital Diaphragmatic Hernia (CDH) - Sujin Gang; Yong Jae Kwon; Hyunhee Kwon; Suhyun Ha; Jueun Park; Byong Sop Lee; Euiseok Jung; Jiyoon Jeong; Soo Hyun Kim; Jung-Man Namgoong (BMC Pediatrics)
Abstract Background Congenital diaphragmatic hernia (CDH) and bronchopulmonary sequestration (BPS) are rare congenital anomalies that can coexist, with studies suggesting that 25–40% of CDH cases are accompanied by BPS. The association between CDH and BPS is thought to arise from embryological disruptions during early gestation, with BPS potentially serving as an anatomical barrier. This study aimed to evaluate the incidence, clinical characteristics, and outcomes of patients with concurrent CDH and BPS at a single institution to improve therapeutic approaches. Methods This study retrospectively analyzed the medical records of neonates diagnosed and treated for BPS concurrent with CDH at Asan Medical Center from 1990 to 2021, identifying 15 cases (3.0%) among 493 CDH patients. Comprehensive data on demographics, treatments, outcomes, diagnostic imaging, and pathological findings were collected and analyzed to explore disease characteristics and evaluate clinical outcomes. Results This study analyzed 15 neonates with concurrent BPS and CDH, with a male predominance (10:5) and an average gestational age of 37.8 weeks, of whom 80% were diagnosed prenatally. CDH repair was performed at a median of 8 days, with no acute repair-related complications observed. In some cases, additional procedures such as hiatal hernia or re-do CDH repair was required, and BPS resection was performed either simultaneous or delayed. Follow-up revealed that most patients grew within the 50th percentile range, with thoracoscopic approaches feasible in over half of the cases, and recurrence-free outcomes achieved in those treated for hiatal hernia or BPS. Discussions No statistical difference in CDH severity was observed between the CDH and CDH + BPS groups, and the clinical outcome of CDH + BPS was better, although the high prevalence of sac-associated CDH types may have confounded the results. Our findings provide additional evidence supporting the protective effect of BPS. However, they also highlight the need for further studies in larger populations to clarify the causal relationship.